A new and previously misidentified Cyrtochilum (Orchidaceae: Oncidiinae) from the high plains of central Ecuador - Dalström, Stig (2015)
A new and previously misidentified, small-flowered Cyrtochilum (Orchidaceae: Oncidiinae) from central Ecuador is described, illustrated with a line drawing and photographs, and compared with the species that it has previously been taxonomically mixed-up with by the author. The new species is readily distinguished by the dark yellow, gibbous and carnose lip callus, versus more elongate, longitudinally furrowed and bilobed calli for similar species.